Influence of Environmental Factors of Influence on the Volume of Financing in the Agro-Industrial Complex - OMARKHANOVA, Zhibek; MISNIK, Olessya; MATAIBAYEVA, Gaukhar; MUKASHEVA, Gulzhan; ZHOLDOYAKOVA, Gulden; RAMAZANOVA, Shynar (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).18, 2022)
The availability of financing for agricultural innovation activities through business loans remains one of the most influential factors in the business environment and entrepreneurship development. A gradual improvement in lending conditions with government intervention will attract more customers to banks, which will allow the SME segment to grow and remain competitive, including in the agro-industrial complex. Agribusiness financing and lending issues are of great importance in financial accounting and taxation, so it is necessary to cover this topic by updating important points. The purpose of the study is to substantiate the theoretical provisions and develop recommendations for improving the accounting for financing and estimating the cost of developing agricultural organizations in the Republic of Kazakhstan.